Peripheral perfusion index and diagnostic accuracy of the post-ROSC electrocardiogram in patients with medical out-of-hospital cardiac arrest. (November 2021) - Compagnoni, Sara; Gentile, Francesca Romana; Baldi, Enrico; Contri, Enrico; Palo, Alessandra; Primi, Roberto; Currao, Alessia; Bendotti, Sara; Ziliani, Paola; Ferrario Ormezzano, Maurizio; Oltrona Visconti, Luigi; Savastano, Simone
Abstract: Aim: A 12-lead electrocardiogram (ECG) after the return of spontaneous circulation (ROSC) is recommended to diagnose a ST-segment elevation myocardial infarction (STEMI). In the early post-ROSC phase, the ECG can show signs of ischemia not necessarily of coronary origin and post-ROSC hypoperfusion could affect ECG reliability. We sought for an association between peripheral perfusion index (PI) values after ROSC and the percentage of false-positive ECG for STEMI. Methods: We considered all the consecutive patients with sustained ROSC after OHCA, admitted to the Fondazione IRCCS Policlinico San Matteo (Pavia) between January 1st, 2015 and December 31st, 2020. ECGs were defined false-positive if meeting the STEMI criteria but without a critical obstructive coronary artery disease worthy of treatment. The mean value of PI over 30 min-monitoring (MPI30) were calculated. Results: Among 351 eligible patients post-ROSC ECG, PI monitoring and an invasive coronary angiography (ICA) were available in 84 cases. The rate of false positive was 16/54 (29.6%) and it differed significantly in the three MPI30 tertiles [T1 (0.2–1): 28.6%; T2 (1.1–2.5): 24.1%; T3 (2.6–6.9): 3.7%, p = 0.04; p for trend = 0.02]. Cardiac arrest duration [OR 1.06 (95 %CI 1–1.1), p = 0.007] and MPI30 [T3 vs T1: OR 0.09 (95 %CI 0.01–0.8), p = 0.03] were significantly associated with the probability of acquiring a false-positive ECG. This association was also confirmed when MPI30 was adjusted for cardiac arrest duration [OR 0.2 (95 %CI 0.1–0.6), p=<0.001]. Conclusions: The rate of false-positive ECG for STEMI after ROSC is related with low perfusion. Our results could help to identify the adequate candidates for an immediate ICA.